Assessment of the safety of a fermented multi-fruit beverage - Sy, Jamie Bernadette A.; Hsu, Tsui-Chun; Liu, Je-Ruei (2020)
Fruits have been widely considered as the "default health foods" as they contain numerous vitamins and minerals needed to sustain human health. To fully enhance their nutritive and flavor features while prolonging their shelf lives, fermentation strategies have been utilized to prepare healthy yet readily consumable fruit products. However, albeit their innumerable health-promoting effects, a lot of people are still concerned if consuming live bacteria and their metabolites are safe for humans. In this study, the safety of a fermented multi-fruit beverage using five different fruits (kiwis, guavas, papayas, pineapples, and grapes) was investigated. Safety assessment experiments performed on the multi-fruit beverage showed that it is nonmutagenic to five strains of Salmonella typhimurium, non-cytotoxic, and is unable to induce chromosome aberrations in Chinese Hamster Ovary K1 (CHO-K1) cells, as well as non-toxic in male ICR mice compared to the water-fed control group after 28 d of feeding. Therefore, these results collectively indicated that the fermented multi-fruit beverage is safe for human consumption.